Consistent criteria for hypotheses testing - Zerakidze, Z. S.; Purtukhiya, O. G. (Ukrains’kyi Matematychnyi Zhurnal, 2019)
We investigate statistical structures that admit consistent criteria for hypotheses testing and establish necessary and sufficient conditions for the existence of consistent criteria for hypotheses testing.